The influence of the rate of selenium crystallization from aqueous solutions on its morphology - Harañczyk I.; Szafirska B.; Fitzner K. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2002)
Selenium crystallization process from aqueous solutions was investigated at constant temperature of 357 K. Two different reducers were used, namely dissolved NaHSO3 and gaseous SO2. Experiments were conducted for solutions with different initial selenium concentration and different pH. The degree of conversion was determined as a function of time from the weight of the sediment, and can be described by Avrami-type equation of the following form: - ln ( 1 - á) = (6.95 . 10 -3 . t )1.52 valid at constant temperature of 357 K for NaHSO3 reducer, rate constant k = 6.95.10-3 min-1, and t in minutes. When the reduction was carried out in SO2 stream, the rate constant k was found to be strongly dependent on the flow rate. Possible mechanism of the reduction process and the influence of the rate of the reduction on the morphology of the product were suggested.